Peregrinação: um novo modo de viver o Sagrado = Pilgrimage: a new way of experiencing the sacred = Peregrinación: una nueva forma de vivir lo sagrado - Nobre, José Aguiar (Teocomunicação, 2024)
This text aims to reflect on the growing phenomenon of the practice of religious pluralism. In particular, pilgrimage to Sanctuaries has become a new way of living the Christian faith, in search of the Sacred. Postmodernity has provided this growing phenomenon in search of spiritual grace and encounter with the Divine in Sanctuaries. These are places of encounter, sociability, fraternity and reconciliation that human beings seek so much today. The fundamental question was thus formulated: how to make a pilgrimage in a deeper and wiser way, to encounter the Sacred in every part of human existence? This study, which follows a bibliographic research methodology, by addressing the origins of pilgrimage in the biblical world, inspired by the pilgrimage of Jesus, seeks to understand how Sanctuaries are privileged places of pilgrimage today. The expected results are limited to the understanding that the theology of pilgrimage can not only favor faith but also opportunities for cultural and religious tourism. Thus, the human being goes on pilgrimage in search of happiness, learning to go to the furthest reaches of his existence. Pilgrimage is the art of living in search of the Sacred.